Influence of iodine on reproductive performance of bucks fed subabul (Leucaena /eucocephala) leaf-meal - RAJENDRAN, D; PATTANAIK, M K; KHAN, S A; BEDI, S P S (The Indian Journal of Animal Sciences, 2014)
The effect of supplementation of iodine on male reproduction of goats, when their diet contained subabul (Leucaena leucocephala) leaf-meal. was assessed using 6 adult bucks (2.5-3 years; 24.4±0.94 kg). The bucks were randomly divided into 2 groups of 3 animals each. viz., control (I0) and iodine supplemented (I100). The animals were fed on a concentrae supplement along with leucaena leaf-meal (LLM). The latter to meet 50% of their CP requirements. Wheat straw was given ad lib. In addition, animals under group I100 received 100 ug of supplemental iodine/head /day. Semen was collected and analyed at monthly intervals during the 3 months of experimental feeding. Plasma samples were analyed for testosterone at the begining and end of the experiment. The results revealed that animals under I100 group maintained their libido throughout the experimental period in contrast to a progressive declie observed in the I0 group. The concentration of spermatozoa (3.25±0.39 vs 2.74±0.24 billion ml-1) and percent live spermatozoa (76.67±1.82 vs 66.17±2.00) were significantly (P<0.01) higher in iodine supplemented (I100) than the non-supplemented bucks (I0). Other semen characteristics, viz. semen volume, pH, number of spermatozoa per ejaculate and mass activity although similar (P>0.05), tended to be higher in I100 group. The initial fructose content, similarly, tended to be higher in I100 than I0 animals. Mean plasma testosterone level was significantly (P<0.04) higher in 1100 than I0 (1.78±0.21 vs 1.14±0.46ng ml-1), The study indicated that supplementation of iodine to leucaena based diet can improve the male reproductive performance of goats.